Influence of different rolling processes on microstructure, texture and anisotropy of the Al–Cu–Li alloy - Fengman Li; Xiangyu Chen; Lipeng Ding; Chenglin Wang; Ke Zhang; Yaoyao Weng; Zhihong Jia (Journal of Materials Research and Technology)
Al–Cu–Li alloys have shown great potential for aerospace application due to their good combination of high strength and low density, but their high planar anisotropy have always hindered their application. In the present work, the influence of different deformation processes, including hot rolling (HR), cold rolling (CR), hot rolling + cold rolling (HR + CR), hot rolling + intermediate annealing + cold rolling (HR + IA + CR) on the microstructure and property anisotropy is systematically investigated for a 2195 Al–Cu–Li alloy. Among the four rolling processes, the HR sample exhibits the lowest yield strength, the highest elongation and the highest anisotropy level. The CR and HR + CR samples have a higher yield strength, decreased elongation and anisotropy level. While the HR + IA + CR sample achieves the combination high yield strength, good elongation and the lowest anisotropy level. The different rolling processes can affect the number density and size of the coarse Al7Cu2Fe phase (>1 μm), which can promote the recrystallization by PSN mechanism. As the number density of Al7Cu2Fe phase in the four samples follow: HR + IA + CR > CR > HR + CR > HR. The HR + IA + CR sample with the highest PSN particles density exhibits highest level of recrystallization and random texture distribution, giving rise to the low anisotropy of the alloy. The low number density of PSN particle and the occurrence of dynamic recrystallization suppress the recrystallization of the HR sample during solution treatment, resulting in strong anisotropy of the alloy. These results can provide key information for optimizing the mechanical properties of Al–Cu–Li alloys for aerospace applications.